Mechanical Characterization of an Aluminum-Composite Hybrid Joint Bonded by Ultrasonic Welding - Lucas, Rafael R. [UNESP]; Mota, Rogério Pinto [UNESP]; da Silva, Francisco J. G.; Botelho, Edson C. [UNESP]; Sales-Contini, Rita C. M. (Springer Nature, 2025)
Plasma Electrolytic Oxidation (PEO) is an advanced surface treatment process for light alloys such as Aluminum, Titanium, Magnesium, and others. It is similar to the anodizing process but uses environmentally friendly electrolytes, such as silicates, aluminates, and phosphates. Due to thermal and plasma phenomena, PEO enables the development of an oxide coating with enhanced physical and chemical properties compared to conventional anodizing. In this study, samples of plasma-anodized AA2024 aluminum alloy were welded to thermoplastic composite PEI/Glass Fiber samples using ultrasonic welding. The welded joint was mechanically characterized by a single lap shear test (based on ASTM D1002:19), and the fractures were evaluated according to ASTM D5573–99 (failure modes). Scanning Electron Microscopy (SEM) was performed on both treated and untreated samples to justify the obtained results. It was observed that the samples treated by the PEO process showed lower shear resistance, around 2.10% less, although regions with interlaminar failure in the composite were found. Additionally, fractures occurred within the oxide coating, indicating overgrowth of the oxide in some regions. SEM analysis revealed that the treated samples did not present pores as observed in the untreated samples, which contributed to fewer mechanical anchoring points between the polymer matrix and the aluminum sample, thereby reducing shear resistance.